Screening of Siddha Medicinal Plants for Anti Cancer Activity - A review - Jeeva Gladys. R, Kalai arasi.R, Elangovan.S, Mubarak.H (Journal of Applied Pharmaceutical Science, 2013)
India is a peninsula of herbal hub, in which Siddha system of medicine has flourished as an enlightment in the field of Medicine. Currently medicinal plants have become the paramount source of drug discovery in research for treating diverse form of diseases including Cancer. In this review Siddha classical literature and evidence based research data were emphasized to explore the Siddha medicinal plants with potent anticancer activity. This literature analysis based on both Siddha philosophy and modern parameters reveals that each medicinal plant has its own specific effects on specific type of Cancer.
Keywords: Anticancer, Siddha, Medicinal plants. &